Spacer Designs for Improved Hydrodynamics and Filtration Efficiency in Sea Water Reverse Osmosis - Sarah Kerdi; Adnan Qamar; Henry J. Tanudjaja; Noreddine Ghaffour (Membranes)
Reverse osmosis (RO) filtration performance is heavily influenced by the design of the feed spacer. Spacer design impacts hydrodynamic patterns within the system, affecting water production and concentration polarization. Two spacer designs, namely pillar (P) and standard (S), were investigated to improve the performance of a commercially available spacer design (C) in the RO process. Two approaches were employed to evaluate spacer performance. First, direct numerical simulation (DNS) was utilized to fundamentally understand the hydrodynamics generated by each spacer design. Second, laboratory RO experiments were conducted to confirm the simulation results. The P and S spacers induced higher flow velocity and vorticity than the C spacer, as confirmed by simulations and experiments. Reduced dead zones were also demonstrated using P and S spacers. However, the standard spacer design exhibited a clear advantage in promoting more efficient mixing within the filtration channels. This enhanced mixing substantially reduced salt concentration at the membrane surface, improving the filtration performance. In agreement with the permeation velocity computation, the S spacer achieved the highest improvement (13%) in both flux yield and specific flux relative to the C spacer. This finding confirms the S spacer’s ability to enhance RO performance while reducing energy consumption.